2022
DOI: 10.3389/fbioe.2022.833122
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Investigation of Natural Rare Earth Metal Chelating Agents From Calothrix brevissima - A Step Towards Unraveling the Mechanisms of Metal Biosorption

Abstract: In this study water soluble compounds that form complexes with Rare Earth Elements (REE) and other metals were isolated from Calothrix brevissima biomass with chromatographic methods for the first time. Molecular characterization showed that the isolated compounds are most likely polysaccharides comprised of arabinose, xylose, mannose, galactose and glucose. FT-IR analysis revealed functional groups involved in the binding mechanism of Tb are likely sulfate- and to a lesser extend hydroxyl-groups. The binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…The samples were analyzed in a Shimadzu HPLC according to Jurkowski et al. [ 31 ] with 25 min runtime per sample.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The samples were analyzed in a Shimadzu HPLC according to Jurkowski et al. [ 31 ] with 25 min runtime per sample.…”
Section: Methodsmentioning
confidence: 99%
“…The solution was filtered with an 0.22 μm filter and mixed with a 0.5 M EDTA solution (sample:EDTA 197:3). The samples were ana-lyzed in a Shimadzu HPLC according to Jurkowski et al [31] with 25 min runtime per sample.…”
Section: Hplc Analysis Of Glycerolmentioning
confidence: 99%
“…As EPS comprise chemically complex polymeric carbohydrates, the monomeric sugar composition of the extracted EPS samples was analyzed using an HPLC-based method. The monomeric sugar composition of the cyanobacterial biomass was determined for all three selected strains following a reported protocol ( Jurkowski et al, 2022 ). Each sample was hydrolyzed with 2% H 2 SO 4 in an autoclave for 1 h at 121°C at 1 bar in order to release monomeric carbohydrate building blocks from the samples constituting polymeric carbohydrates.…”
Section: Methodsmentioning
confidence: 99%
“…However, at present, there is no discrete chemical entity that has been identified as dominant cell wall feature that governs metal binding. In a previous study, for instance, it was shown that complex polymeric sugars are involved in the adsorption of terbium by C. brevissima (Jurkowski et al, 2022). Cell wall-derived binding entities most likely vary for every organism and metal presented.…”
Section: Metal Adsorption Experimentsmentioning
confidence: 96%